Recent advances in the understanding of brown spider venoms: From the biology of spiders to the molecular mechanisms of toxins - Gremski, Luiza Helena; Trevisan-Silva, Dilza; Ferrer, Valeria Pereira; Matsubara, Fernando Hitomi; Meissner, Gabriel Otto; Martins Wille, Ana Carolina; Vuitika, Larissa; Dias-Lopes, Camila; Ullah, Anwar [UNESP]; Moraes, Fabio Rogerio de [UNESP]; Chavez-Olortegui, Carlos; Barbaro, Katia Cristina; et al. (Elsevier B.V., 2014)
The Loxosceles genus spiders (the brown spiders) are encountered in all the continents, and the clinical manifestations following spider bites include skin necrosis with gravitational lesion spreading and occasional systemic manifestations, such as intravascular hemolysis, thrombocytopenia and acute renal failure. Brown spider venoms are complex mixtures of toxins especially enriched in three molecular families: the phospholipases D, astacin-like metalloproteases and Inhibitor Cystine Knot (ICK) peptides. Other toxins with low level of expression also present in the venom include the serine proteases, serine protease inhibitors, hyaluronidases, allergen factors and translationally controlled tumor protein (TCTP). The mechanisms by which the Loxosceles venoms act and exert their noxious effects are not fully understood. Except for the brown spider venom phospholipase D, which causes dermonecrosis, hemolysis, thrombocytopenia and renal failure, the pathological activities of the other venom toxins remain unclear. The objective of the present review is to provide insights into the brown spider venoms and loxoscelism based on recent results. These insights include the biology of brown spiders, the clinical features of loxoscelism and the diagnosis and therapy of brown spider bites. Regarding the brown spider venom, this review includes a description of the novel toxins revealed by molecular biology and proteomics techniques, the data regarding three-dimensional toxin structures, and the mechanism of action of these molecules. Finally, the biotechnological applications of the venom components, especially for those toxins reported as recombinant molecules, and the challenges for future study are discussed. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Brown spider; Loxosceles; Venom; Toxins; Loxoscelism; Dermonecrosis